DIFFERENCES IN MOTOR ABILITIES OF SUCCESSFUL AND LESS SUCCESSFUL GROUPS OF BASKETBALL PLAYERS FROM 12 TO 14 YEARS OLD - Aleksa Stanković; Nermin Salkanović; Alem Kukić (Sport Scientific And Practical Aspects, 2025)
The research is based on a sample of 132 cadet basketball players (the more successful group counts 69, and the less successful 63 respondents) from 12 participating clubs of the Sarajevo Canton cadet basketball league. The set of variables in this research is composed of 12 motor tests. Among the motor tests for evaluating locomotor speed, agility and reflex power, the following tests were applied: time to run sections of 5, 10, 15, and 20 m, T - agility test, Line agility test, Zig - Zag agility test, vertical reflection on feet - hands on to the side (sqaut jump), vertical reflection on the feet with a swing of the hands (sqaut hand free jump), vertical reflection after jumping from a height of 40 cm (drop jump), 10 consecutive vertical reflections on the feet (repeating vertical jumps), one-legged horizontal jump from a standing position (standing long jump). After determining, i.e. adjusting the data values to characteristics that are suitable and valid for the use of designed analyzes and providing exact answers to the defined hypotheses, the following procedures were used for data processing and analysis in this paper: measure of central tendency, variability and shape of distribution of 12 motor tests, univariate F tests to determine the classification of respondents into groups based on the level of success, multivariate analysis of variance (Manova) to determine the differences between groups of successful and less successful basketball players in terms of motor skills. The information and results obtained from the analyzes can serve as a basis for modeling programs for the recognition of talents in basketball